Workers empowerment relationship with job involvement Field study at Sonelgaz power plant of JijeL - Sayoud, Aziz; Belaieur, Tahar (Journal of Human Sciences, 2021)
This study examines the relationship between empowerment and job involvement by measuring the level of workers’ empowerment in the dimensions of participatory administration, working group, job incentives and job involvement through its mental, emotional and behavioral dimensions. The study adopted the comprehensive survey of 289 workers at Sonelgaz power plant of Jijel, a simple observation tools and a 30-items form reflecting the empowerment and job involvement dimensions, designed according to the Fifth Likert Scale, with a specific item on the job level of the subject of research. The study found a strong positive correlation between participatory administration and mental involvement, and between worker group and emotional involvement, as well as between work incentives and behavioral involvement, Therefore, the relationship between empowerment and job involvement is positive and strong in the target station.